2000
DOI: 10.1016/s0030-3992(00)00010-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of absorption length of CO2 and high power diode laser radiation for ordinary Portland cement and its influence on the depth of melting

Abstract: The laser beam absorption lengths of CO 2 and a high power diode laser (HPDL) radiation for concrete have been determined. By employing Beer-Lambert's law the absorption lengths for concrete of CO 2 and a HPDL radiation were 470±22 µm and 177±15 µm respectively. Indeed, this was borne out somewhat from a cross-sectional analysis of the melt region produced by both lasers which showed melting occurred to a greater depth when the CO 2 laser was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Moreover, this expression has been shown to be completely applicable to other composite and ceramic materials [23][24][25]. It is important to realise that the validity of (1) rests on the assumption that the plume species resulting from material removal absorb the laser beams in a similar manner to the solid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this expression has been shown to be completely applicable to other composite and ceramic materials [23][24][25]. It is important to realise that the validity of (1) rests on the assumption that the plume species resulting from material removal absorb the laser beams in a similar manner to the solid.…”
Section: Resultsmentioning
confidence: 99%
“…Also, probable changes in the absorption level of the material as removal progresses are not taken in account by (1). Nonetheless, as the work of 6 Andrew et al [27], Schmidt et al [16] and Lawrence et al [23][24][25] demonstrated, this simple form of the expression is quite adequate as a first approximation. Also, according to Bäuerle [26] the expression is applicable to ablation processes which are either photophysical or photochemical in nature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these figures it is reasonable to assume that since the CO 2 laser beam is absorbed to a greater depth, then the melt depth will be more and the resulting meltpool will be larger and will therefore cool at a slower rate than that of the HPDL generated meltpool. Such a observation was made during similar investigations on ordinary Portland cement (OPC) carried out by Lawrence and Li [36,37]. If one considers the theories of constitutional supercooling and morphological stability [38][39][40][41], which are illustrated schematically in Fig.…”
Section: Comparative Analysis Of the Co 2 And High Power Diode Laser mentioning
confidence: 93%
“…In comprehensive investigations, Lawrence and Li compared the e V ects of CO 2 , Nd :YAG, excimer and HPDL radiation on the wettability characteristics of an Al 2 O 3 /SiO 2 based ceramic [35], a mild steel [36,37] and selected biomedical polymer (PMMA) [38], noting that changes in the wettability characteristics of the ceramic and the steel varied depending upon the laser type. In addition, Lawrence and Li carried out a comparative study of the characteristic of the glazes generated on the surface of concrete with the CO 2 laser and the HPDL [39,40], as well as determining the absorption depths of CO 2 and HPDL beams in ordinary Portland cement [41,42] and an Al 2 O 3 -based refractory [43].…”
Section: Introductionmentioning
confidence: 99%